How does satisfaction with the health-care system relate to patient experience? - Sara N Bleich; Emre Özaltin; Christopher JL Murray
OBJECTIVE: To explore what determines people's satisfaction with the health-care system above and beyond their experience as patients. METHODS: Data on health system responsiveness, which refers to the manner and environment in which people are treated when they seek health care, provides a unique opportunity to better understand the determinants of people's satisfaction with the health-care system and how strongly this is influenced by an individual's experience as a patient. The data were obtained from 21 European Union countries in the World Health Survey for 2003. Additive ordinary least-squares regression models were used to assess the extent to which variables commonly associated with satisfaction with the health-care system, as recorded in the literature, explain the variation around the concept of satisfaction. A residual analysis was used to identify other predictors of satisfaction with the health-care system. FINDINGS: Patient experience was significantly associated with satisfaction with the health-care system and explained 10.4% of the variation around the concept of satisfaction. Other factors such as patient expectations, health status, type of care, and immunization coverage were also significant predictors of health system satisfaction; although together they explained only 17.5% of the observed variation, while broader societal factors may largely account for the unexplained portion of satisfaction with the health-care system. CONCLUSION: Contrary to published reports, people's satisfaction with the health-care system depends more on factors external to the health system than on the experience of care as a patient. Thus, measuring the latter may be of limited use as a basis for quality improvement and health system reform.